An Analysis of Speaking Difficulties Among Class 10B Students at Ahmad Syarifuddin Islamic School: An Analysis of Speaking Difficulties Among Class 10B Students at Ahmad Syarifuddin Islamic School - Dewi halimatus sya’ diyah (Journal of Innovative and Creativity, 2025)
This study investigated the difficulties in speaking English among tenth-grade (B) students at Islamic senior high school Ahmad Syarifuddin tahfidz, an Islamic boarding school emphasizing qur’anic memorization. The research aimed to identify the main challenges students faced, the factors that influenced their speaking difficulties, and how the pesantren environment affected their motivation and opportunities to speak English. Using a qualitative case study approach, data were collected through observations, interviews, and documentation. The findings revealed that students struggled with limited vocabulary, incorrect pronunciation, weak grammar mastery, and low self-confidence. Internal factors such as anxiety and fear of making mistakes, along with external factors like a non-English-speaking environment and limited time due to tahfidz activities, significantly hindered speaking development. The study concluded that students' English-speaking abilities were affected by both psychological barriers and the unique constraints of their religious educational setting. The findings were expected to inform educators and institutions about the contextual challenges of language learning in pesantren environments.